Marketing Strategy of Islamic Education Institutions in increase the number of students (Case Study In SD Muhammadiyah Ponorogo) (Universitas Pamulang, 2025)
This study aims to describe: 1) the marketing strategy planning of Islamic educational institutions to increase student numbers (a case study at Muhammadiyah Elementary School in Ponorogo), 2) the implementation of marketing strategies for Islamic educational institutions to increase student numbers (a case study at Muhammadiyah Elementary School in Ponorogo), and 3) the results of marketing strategies for Islamic educational institutions to increase student numbers (a case study at Muhammadiyah Elementary School in Ponorogo). The research method used was a qualitative case study. Data collection and compilation in this study included observation, interviews, and documentation. Primary data sources were obtained from observations, interviews with the principal, vice principal for student affairs, public relations officers, teachers, and documentation. The results of this study include: 1) the planning process, including establishing the PPDB schedule, determining targets, time, and location, and selecting promotional media, both online and offline. In addition, the school also offered various scholarships to attract community interest. 2) the strategy implementation was carried out sustainably through various school activities, such as kindergarten competitions, school anniversary celebrations, and flagship programs. Social media is also used as an effective and efficient promotional tool, 3) increasing the number of students, namely the number of students from 2021-2022 was 109 students, 2022-2023 was 116 students, in 2023-2024 there were 142 students, in 2024-2025 there were 127 students.